An initial study on chemical constituents of Bischofia javanica - Thi Mai, Nguyen (Vietnam Journal of Science and Technology, 2017)
From the methanol extract of Bischofia javanica leaves, five compounds including 5'-b-D-glucopyranosyloxyjasmonic acid methyl ester (1), 2-(4-hydroxy-3-methoxyphenyl)ethyl-O-β-D-glucopyranoside (2), hexyl-O-β-D-glucopyranoside (3), friedelan-3-one (4), and gallic acid (5) were isolated. Their structures were elucidated by NMR spectra as well as in comparison with previous reported data. This is the first report of 1 and 2 from Bischofia javanica